HUBUNGAN MORAL INTEGRITY DAN KECEMASAN SOSIAL DENGAN ACADEMIC DISHONESTY REMAJA AKHIR - Untung Subroto Darmawan; Agoes Dariyo (Fakultas Psikologi Universitas Tarumanagara, 2017)
Aim of this research are to investigate the impact of friendship and emotion intelligence on the life satisfaction of adolescence. 102 adolescences involve in the research. Data collecting by questionaries such as moral integrity, social anxiety and academic dishonesty. Multiple correlation was used to analysis the data. The findings suggest that there is no correlation moral integrity and academic dishonesty of adolescences, there is correlation between social anxiety and academic dishonesty, and there is no correlation between moral integrity and social anxiety. Keywords: moral integrity, social anxiety, academic dishonesty, late adolescence